2020
DOI: 10.3390/ma13020361
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Organic Acid Pretreatment of Eucalyptus for Kraft Dissolving Pulp Production

Abstract: Pretreatment is an essential process for the extensive utilization of lignocellulose materials. The effect of four common organic acid pretreatments for Kraft dissolving pulp production was comparatively investigated. It was found that under acidic conditions, hemicellulose can be effectively removed and more reducing sugars can be recovered. During acetic acid pretreatment, lignin that was dissolved in acetic acid could form a lignin-related film which would alleviate cellulose hydrolysis, while other organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…In addition, close to 220 g of the DES was obtained by rotary ev oration treatment, which is conducive to the reuse of the DES. Based on the initial mas wheat straw, the total recovery reached 72%, which is significantly higher than that previous study [47].…”
Section: Pulp Bleachingcontrasting
confidence: 70%
“…In addition, close to 220 g of the DES was obtained by rotary ev oration treatment, which is conducive to the reuse of the DES. Based on the initial mas wheat straw, the total recovery reached 72%, which is significantly higher than that previous study [47].…”
Section: Pulp Bleachingcontrasting
confidence: 70%
“…Controlling the surface chemical composition of biochars through functionalization offers high added-value applications to low-cost, or negative-cost biomass residues. It has been shown that some biochar materials, despite a low surface area, can have very high adsorption capacities due to their high surface functionality [22,23]. Therefore, the application of organic acids for the functionalization of biochars can be an economically viable and environmentally friendly method to enhance the adsorption capacity of biochar [19].…”
Section: Introduction and State Of The Artmentioning
confidence: 99%